Promo Dompet Digital dan Israf Mahasiswa: Analisis Perilaku Konsumtif Generasi Z - Tantowi, Ahmad; Putri Sarsono, Ismei Affianny; Anwar, Rosikhan (Universitas Islam Kadiri, 2025)
The use of digital wallets among students is growing rapidly and provides ease of transactions, but it also triggers consumptive behavior. This study aims to analyze the consumptive behavior of students using digital wallets in Kendal Regency and review it from the perspective of sharia economics. The research approach used is qualitative descriptive with interview and questionnaire methods. The data was analyzed using inductive techniques through the stages of collection, reduction, and interpretation. The results showed that 82% of college students have consumptive tendencies, characterized by impulse purchases, the use of promotions without considering needs, and the use of digital wallets for non-priority consumption. Environmental, lifestyle, psychological, and friendship factors have been shown to encourage this behavior. Sharia economic analysis confirms that this behavior is contrary to the principles of proportionality, responsibility, and the prohibition of israf (excess) and tabdzir (waste). This study recommends Islamic financial literacy and Islamic value-based education as an effort to reduce student consumptive behavior. These findings make a theoretical contribution to the study of digital financial behavior and practical implications for universities, society, and financial regulators.